Prevalence of Persistent Pain after Total Knee Arthroplasty and the Impact of Neuropathic Pain - Hasegawa, Masahiro; Tone, Shine; Naito, Yohei; Wakabayashi, Hiroki; Sudo, Akihiro (The Journal of Knee Surgery, 2019)
The present study aimed to define the prevalence of pain persisting after total knee arthroplasty (TKA) and determine the impact of neuropathic pain. Knee pain after TKA was evaluated in 154 patients (222 knees with osteoarthritis) using a numerical rating scale (NRS) and followed up for a mean of 4.7 years. The patients were classified according to whether they had no or mild pain (NRS ≤ 3), or moderate-to-severe pain (NRS > 3), and then assigned to groups with nociceptive, unclear, or neuropathic pain based on responses to painDETECT questionnaires. Risk factors for these types of pain were determined. The ratio of patients with moderate-to-severe pain was 28% (62 knees). Thirteen patients (21 knees; 9%) experienced unclear pain. Patients with moderate-to-severe or unclear pain had malalignment and lower Knee Society knee scores. In conclusion, a significant number of patients experienced moderate-to-severe and unclear pain after TKA. Moderate-to-severe pain was associated with unclear pain.
Keywords: total knee arthroplasty; neuropathic pain; patient satisfaction; alignment